Induced abortion on demand and birth rate in Sami-speaking municipalities and a control group in Finnmark, Norway - Norum, Jan; Svee, Tove Elisabeth; Heyd, Anca; Nieder, Carsten (International Journal of Circumpolar Health, 2013)
Objectives. The objective of this study was to analyze the birth and induced abortion on demand (IAD) rate among women in Sami-speaking communities and a control group in Finnmark County, Norway. Methods. The 6 northern municipalities included in the administration area of the Sami language law (study group) were matched with a control group of 9 municipalities. Population data (numbers, sex and age) were accessed from Statistics Norway. Data on birth rate and IAD during the time period 1999 2009 were derived from the Medical Birth Registry (MBR) of Norway. Data on number of women in fertile age (15 44 years) were obtained from Statistics Norway. Between 2001 and 2008, this age group was reduced by 12% (Sami) and 23% (controls), respectively. Results. Finnmark County has a high IAD rate and 1 in 4 pregnancies (spontaneous abortions excluded) ended in IAD in the study and control groups. The total fertility rate per woman was 1.94 and 1.87 births, respectively. There was no difference between groups with regard to the IAD/birth ratio (P 0.94) or general fertility rate GFR (P 0.82). Conclusions. Women in the Sami-majority area and a control group in Finnmark County experienced a similar frequency of IAD and fertility rate.